Towards deciphering the Cenozoic evolution of the East Pisco Basin (southern Peru). Issue 2 (1st December 2022) - Di Celma, C.; Pierantoni, P.P.; Volatili, T.; Molli, G.; Mazzoli, S.; Sarti, G.; Ciattoni, S.; Bosio, G.; Malinverno, E.; Collareta, A.; Gariboldi, K.; Gioncada, A.; et al.
ABSTRACT: The Cenozoic succession of the East Pisco Basin preserves the sedimentary record of several episodes of deformation of the forearc crust along the Peruvian margin. The 1:50, 000 scale geological map presented here encompasses an area of about 1, 000 km 2 lying astride the Ica River, and contributes to our understanding of the timing and mode of basin filling and deformation. Our novel two-fold megasequence framework provides a sound basis for establishing a first-order tectono-stratigraphic setting of the mid-Eocene–upper Miocene succession exposed in the study area. We interpret that the mid-Eocene to lower Oligocene succession studied in this work (megasequence P) was deposited in a single forearc basin, which was dissected into the present-day West and East Pisco basins by a fault-bounded basement high during the late Oligocene, and subsequently overlain by the Miocene fill of the East Pisco basin (megasequence N).